2016
DOI: 10.1071/ma16009
|View full text |Cite
|
Sign up to set email alerts
|

Free living amoebae and human disease

Abstract: Pathogenic FLA are ubiquitous protozoans and despite frequent human contact remain a rare cause of often devastating infection with poor prognosis. Given changes in climate, human encroachment into the environment, increasing immunosuppression, and improving diagnostic capacity, it is likely we will see increased cases in the future. Early diagnosis is challenging but crucial to achieving a favourable outcome. It is best facilitated by improved awareness of FLA disease, appropriate clinical suspicion and early… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…In this study, Acanthamoeba infection diagnosis and Acanthamoeba keratitis prognosis in non-contact lens wearers were both greatly improved by the use of PCR tests. It allows more rapid diagnosis with small samples, and although it increases the sensitivity diagnostic, requires specialized laboratories 13,14 .…”
Section: Resultsmentioning
confidence: 99%
“…In this study, Acanthamoeba infection diagnosis and Acanthamoeba keratitis prognosis in non-contact lens wearers were both greatly improved by the use of PCR tests. It allows more rapid diagnosis with small samples, and although it increases the sensitivity diagnostic, requires specialized laboratories 13,14 .…”
Section: Resultsmentioning
confidence: 99%
“…Main findings/outcomes Bastida et al (2016) Omics used for studying the catabolic pathways in Sphingomonadeles aid in compost bioremediation Yoneda et al (2016) To enhance the phenolic tolerance and accumulation of lipid in Rhodoccus opacus transcriptomics has been found quite an effective omics approach Bursle and Robson (2016) Nonculture diagnostic techniques allows detection of organism that are current difficult or impossible to culture Bargiela et al (2015) Metabolome-based techniques can be used to predict microbial activities; to comprehend their functional inputs to environments in which they thrive Krumsiek et al (2015) From such an investigation, it was revealed that metabolomics approach can significantly be applied to monitor the hazardous waste and the consequences associated with it microRNA levels can also be used to investigate the gene expression regulation. MicroRNAs are noncoding RNA molecules regulating the mRNA transcription process and are crucial for a variety of gene expression patterns (Pritchard et al, 2012).…”
Section: Referencementioning
confidence: 99%
“…Free-living amoebae (FLA) of the genus Acanthamoeba are cosmopolitan protozoans commonly found in natural environments, they play a significant ecological role in controlling bacterial populations. Some species of this genus, in addition to being ecologically relevant, are also important in the medical field, due to their ability to exist as free-living organisms and as parasites, becoming a threat to the health and life of the hosts [ 1 , 2 ]. In the cornea, Acanthamoeba are etiological agents of Acanthamoeba keratitis (AK), a painful, vision–threatening infection occurring primarily in immunocompetent persons and contact lens users [ 3 ].…”
Section: Introductionmentioning
confidence: 99%